Transisi Menuju Batik Ramah Lingkungan: Pemanfaatan Serat Alam sebagai Media Alternatif dan Penerapan Konsep Zero Waste - Yustiana Dwirainaningsih; Mursidah; Andri Nur Cahyo; Aria Mulyapradana (Edusight Jurnal Pengabdian Masyarakat, 2026)
The batik industry's dependence on conventional textile raw materials and production patterns that produce high waste (fast fashion) poses serious challenges to environmental and sustainability aspects. This Community Service (PkM) activity aims to facilitate the transition towards more environmentally friendly batik production in the Independent Women's Community. The implemented solutions focus on two main pillars: (1) Substitution of Conventional Media with Sustainable Natural Fibers and (2) Application of Zero Waste Fashion Principles in design and production. The PkM method involves intensive training, technical assistance, and demonstrations of batik making on natural fiber media (pineapple fiber) as well as zero waste cutting pattern design workshops. The results of the activity demonstrated a significant increase in partners' understanding and skills in processing natural fibers into high-quality batik materials, while also enabling them to design fashion products that minimize fabric waste to below 5%. This implementation successfully created a prototype batik product with high sales value, based on renewable materials, and aligned with green market demands. Overall, this Community Service Program not only increased the technical and economic capacity of the Independent Women's Group but also demonstrated that a sustainable and waste-free batik production model is realistic and feasible, making a real contribution to environmental preservation and the development of a responsible creative economy.